Adherence to the Dutch Guidelines for a Healthy Diet and cancer risk in the European Prospective Investigation into Cancer and Nutrition–Netherlands (EPIC-NL) cohort. Issue 11 (6th November 2013) - Struijk, Ellen A; May, Anne M; Beulens, Joline WJ; Fransen, Heidi P; de Wit, G Ardine; Boer, Jolanda MA; Onland-Moret, N Charlotte; Hoekstra, Jeljer; van der Schouw, Yvonne T; Bueno-de-Mesquita, H Bas; Peeters, Petra HM
Abstract: Objective: To examine the association between adherence to the Dutch Guidelines for a Healthy Diet created by the Dutch Health Council in 2006 and overall and smoking-related cancer incidence. Design: Prospective cohort study. Setting: Adherence to the guidelines, which includes one recommendation on physical activity and nine on diet, was measured using an adapted version of the Dutch Healthy Diet (DHD) index. The score ranged from 0 to 90 with a higher score indicating greater adherence to the guidelines. We estimated the hazard ratios (HR) and 95 % confidence intervals for the association between the DHD index (in tertiles and per 20-point increment) at baseline and cancer incidence at follow-up. Subjects: We studied 35 608 men and women aged 20–70 years recruited into the European Prospective Investigation into Cancer and Nutrition–Netherlands (EPIC-NL) study during 1993–1997. Results: After an average follow-up of 12·7 years, 3027 cancer cases were documented. We found no significant association between the DHD index (tertile 3 v . tertile 1) and overall (HR = 0·97; 95 % CI 0·88, 1·07) and smoking-related cancer incidence (HR = 0·89; 95 % CI 0·76, 1·06) after adjustment for relevant confounders. Excluding the components physical activity or alcohol from the score did not change the results. None of the individual components of the DHD index was significantly associated with cancer incidence. Conclusions: In the present study, participants with a high adherence to the Dutch Guidelines for a Healthy Diet were not at lower risk of overall or smoking-related cancer. This does not exclude that other components not included in the DHD index may be associated with overall cancer risk.